HEALTH PROMOTING BEHAVIORS AMONG OLDER PEOPLE LIVING ALONE WITH CHRONIC DISEASE IN THE LOWER NORTHERN REGION OF THAILAND - Noosorn, Narongsak; Saengngern, Sanae (European Scientific Journal, ESJ, 2013)
Background: Old age is the period of life when people suffer from a variety of degenerative conditions. Objectives: This study investigates a population of over-60s in a rural Thai province to examine the relationships between living alone, health-related behaviours and incidence of chronic illness. Methods: This study was descriptive study. All of population were purposively selected in this study included 572 of over-60s , who had presented for treatment during January 7 to August 6, 2011 at five community “health promotion” hospitals in Kong Krailat district, in Thailand. The research employed a purpose-designed structured interview. Possible associations between presence of healthy and unhealthy behaviours and reported health status were examined using logistic regression analysis and odds ratios (OR), confidence intervals (CI), and chi-square results were calculated. Results: Those living alone were somewhat more likely to be socially isolated, have high-fat diets, and engage in low levels of regular physical activity. However after controlling for confounding variables, significant associations were found only between living alone and high alcohol use and problems in managing stressful life events. Older people living alone were more than twice as likely to use alcohol to hazardous levels as those living with a caregiver and more than twice as likely to report difficulty in managing stressful life events. The likelihood of depression as diagnosed by a hospital physician or nurse was 4.82 times higher in those living alone (OR =3.96, 95% confidence interval [CI] = 1.1 to 13.4). Conclusion: Given the results of this study, we suggest that increased attention must be focused on the interaction between alcohol use, coping with stress and depressive illness.